The bell jar - Plath, Sylvia (Harper Perennial modern classics., 2006)
This novel--echoing Plath's own experiences as a rising writer/editor in the early 1950s--chronicles the nervous breakdown of Esther Greenwood: brilliant, beautiful, enormously talented, successful, but slowly going under, and maybe for the last time.